Perlindungan Kehormatan dalam Aturan Pandangan dan Sentuhan antar Mahram Menurut Mazhab Syafi‘i - Husnul Furqon; Muhammad Amar Adly (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This article examines in depth the concept of protecting human dignity through the regulation of gaze and physical contact among mahram according to the Shafi‘i School of Islamic law. From an Islamic perspective, the preservation of dignity (ḥifẓ al-‘irḍ) occupies a highly fundamental position as part of the objectives of Islamic law, particularly in regulating social relations and family interactions. Although mahram relationships legally allow closer interaction, Islam continues to establish ethical boundaries to safeguard purity and moral values. This study is a normative legal research employing conceptual and normative-fiqh approaches, relying on primary sources such as the Qur’an, the Prophetic traditions (hadith), and classical as well as contemporary Shafi‘i jurisprudential literature. The findings indicate that the Shafi‘i School does not regard mahram relations as a sphere of absolute and unrestricted freedom, but instead provides clear regulations concerning gaze and physical contact. Visual interaction is permitted in a limited manner, restricted to certain parts of the body and subject to the condition that it does not provoke desire or potential moral temptation (fitnah). Meanwhile, physical contact is regulated more strictly and, in principle, is only permitted in situations of legitimate shar‘i necessity, such as medical treatment or emergency circumstances. Therefore, the regulation of gaze and physical contact among mahram in the Shafi‘i School functions as an instrument for protecting human dignity, preserving the sanctity of family relationships, and preventing behavioral deviations from an early stage.